First SHRIMP U-Pb and 40Ar/39Ar chronological results from impact melt breccia from the Paleoproterozoic Dhala impact structure, India - Pati, J.; Jourdan, Fred; Armstrong, R.; Reimold, W.; Prakash, K. (Geological Society Publishing House, 2010)
The ~11-km-wide Dhala impact structure, in north-central India, is located in Archean granitoids of the Bundelkhand craton and is partially exposed beneath Paleoproterozoic sediments belonging to the Vindhyan Supergroup, which place the age of the structure between ca. 2.5 Ga and ca. 1.7 Ga. Field mapping and extensive drill-core observations show that an originally coherent impact melt sheet up to 130 m thick was spread over more than 12 km2. Confirmation of the impact origin of the structure is based on the recognition of diagnostic shock metamorphic features in clasts in impact melt rock. In order to better constrain the age of the impact event, a geochronological study was undertaken of the Dhala impact melt breccia, involving 40Ar/ 39Ar step-heating and sensitive high-resolution ion microprobe (SHRIMP) U-Pb dating techniques that were applied to surface and subsurface samples. The U-Pb data for two samples yield ages of 2563 Ma and 2553 Ma, which indicate the age of the granitoid basement. The 40Ar/39Ar experiments resulted in partial plateau ages that indicate that the Dhala impact melt rock was affected by a strong thermal/hydrothermal overprint at ca. 1 Ga. SHRIMP U-Pb ages for two zircon overgrowths indicate a ca. 530 Ma event that could have contributed to the post-impact resetting of the impact melt rock. The results indicate a common problem experienced when attempting to date small-to moderately sized impact events. Further analysis is planned. © 2010 The Geological Society of America. All rights reserved.